2019
DOI: 10.1016/j.envres.2019.108613
|View full text |Cite
|
Sign up to set email alerts
|

Development of a questionnaire-based insecticide exposure assessment method and comparison with urinary insecticide biomarkers in young Australian children

Abstract: Development of a questionnaire-based insecticide exposure assessment method and comparison with urinary insecticide biomarkers in young Australian children, Environmental Research (2019), doi: https://doi.insecticides 22 23 24 25 26ƩnsOP concentrations were lower when fruits and vegetables were always or almost always washed 35 prior to cooking or eating (β: -0.69 95% CI: -1.25, -0.12). In multivariable modelling 3-PBA 36 concentrations were also associated with hand-washing frequency (β: 1.69 95% CI: 0.76, 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…The pyrethroid burden depends on dietary habits (fruit and vegetable consumption) and smoking status but also domestic pesticide use, the presence of an animal in the household, and handwashing frequency 4,110,127,130 . Adults are contaminated mostly by dietary ingestion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pyrethroid burden depends on dietary habits (fruit and vegetable consumption) and smoking status but also domestic pesticide use, the presence of an animal in the household, and handwashing frequency 4,110,127,130 . Adults are contaminated mostly by dietary ingestion.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of handwashing varies according to the pesticide used 149 . Moreover, a cross‐sectional study of 56 children younger than 2 years in Australia showed that handwashing more than 3 times a day was associated with lower levels of urinary pesticide metabolites ( LE4 ) 130 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…β‐Cypermethrin (β‐CYP) is a widely applied type‐II pyrethroid insecticide. Due to its excessive usage, β‐CYP and its metabolites have been detected in environmental matrices (Mehler et al, ; Tang et al, ) and sometimes even accumulate in the bodies of humans or mammals through food chains (English et al, ). Therefore, the toxic effects of β‐CYP have received much attention from the public.…”
Section: Introductionmentioning
confidence: 99%